Risiko Harga Sayuran Masa Pandemi Covid 19 Di Kota Serang - Ratna Mega Sari; Andjar Astuti; Asih Mulyaningsih; Ari Tresna Sumantri; Setiawan Sari Yoga (JURNAL AGRIBISNIS TERPADU, 2021)
Vegetable Price Risk During Covid-19 Pandemic in Serang City. This research aims to analyze price risk of vegetables during pandemic period in Serang City and to identify risk sources of high price risk vegetables in Serang city. Research was conducted by using secondary data from central bureau of statistic of Banten. Risk level was obtained by variation coefficient analysis through variance and standard deviation analysis. Identification of risk sources is conducted descriptively. Analysis result show that vegetables with high price risk with variation coefficient are spinach (0.058), long beans (0.052), potato (0.057), cucumber (0.094), cabbage (0.116), chayote (0.056), bean sprouts (0.059), long eggplant (0.051) and tomato (0.119). It can be concluded that tomato is vegetable with the highest risk which is followed by cabbage, cucumber, bean sprouts, spinach, potato, long beans, and long eggplant.Risk sources are generally caused by vegetables character which is typically perishable and supply fluctuations which is caused by pandemic condition.